(untitled) (Palíndromo, 2026)
This article proposes analyzing different versions of the sublime produced by art in response to contact with the Amazon rainforest between the 19th and 20th centuries. The central hypothesis is that, in all of them, ecological thought is reconciled with a markedly romantic perspective. This derives mainly from the 19th-century travelogues, in which the aesthetic dimension plays a prominent role in the construction of an environmental discourse. It combines the vision of nature as an organic totality, essentially romanticist, with the practical and political reasons that underlie the future science of ecology. Starting from a general consideration of the configuration of the Amazon as a source of this simultaneously aesthetic and ecological experience, it presents the following case studies: a comparison between the accounts of travelers Francis de Castelnau and Paul Marcoy to the Amazon at the end of the 19th century and the illustrations made by Oswaldo Goeldi for the book Cobra Norato, by Raul Bopp, in 1937. These studies show how travel, accounts, and images have symbolically constructed Amazonian nature as a locus of modern sensory experiences, especially of the ecological sublime.